Visages de la biodiversité marine - Pierre Brunel (VertigO, 2005)
The huge variety of plants, animals and microbes, their genes and the landscapes that they build, all these components of the living world – or « biosphere » - on our planet make up its biodiversity (or biological diversity), so-called since about 1985. The bulk of this diversity is unseen by most people since a huge majority of these living organisms are too small and hidden in vegetation, in soil, in coral reefs, in muds and sands covering the bottom of oceans, lakes and rivers. Many of these organisms are nonetheless indispensable to the well-being of humans, either directly as renewable resources with market value, or indirectly for maintaining a certain ecological equilibrium in present-day nature. This balance is presently being broken in many places on our planet because industrial Man has eradicated too many species supplying ecological services. The latter are ignored by his myopic accounting bothered only by the monetary value of immediate goods and services. Planetary biodiversity can be viewed under four components, that of species, that of high-level taxonomic groups, that of their genetics, and that of ecosystems and their functions and services for humanity. Methods necessary to gain knowledge on those four types of living variety are summarized. The diversity of marine species is harder to know than that of terrestrial or freshwater species, which is probably greater, but high-level biodiversity is much greater in the oceans. Figures are given to demonstrate that of the main animal phyla and classes, together with examples of new and recent discoveries at these levels. Marine ecological biodiversity is illustrated first by the major ways of life (plankton, nekton, benthos and parasites), and afterwards by the large groups of species with different geographic distributions determined by present-day temperatures but strongly influenced by the evolutionary history of the earth. Ecosystems are a third kind of functional organization of microbial, plant and animal communities which are deeply structured by depth and light in the sea. Present knowledge on marine genetic biodiversity rests heavily on species with short-term usefulness, but great progress is being made on the phylogeny of high-level taxa, and modern molecular techniques promise to complement traditional morphological methods to identify species. To counter current grave threats to marine biodiversity, collective and individual actions are now urgent. Examples are those of shifting protection priorities from vulnerable species toward whole vulnerable ecosystems, and managing entire marine ecosystems instead of only their abundant commercial species.